Reading Roman declamation : the declamations ascribed to Quintilian - Dinter, Martin T.; Guérin, Charles; Martinho, Marcos (Beiträge zur Altertumskunde., 2016)
As a genre situated at the crossroad of rhetoric and fiction, declamatio offers the freedom to experiment with new forms of discourse. Placing the literariness of (Ps0Quintillian's oeuvre into the spotlight, this volume showcases declamation as a realm of genuine literary creation with its own theoretical underpinning, literary technique and generic conventions. It is of interest to students and scholars of rhetoric and Roman Literature.